Understanding diagnostic disagreement in angle closure assessment between anterior segment optical coherence tomography and gonioscopy. Issue 6 (6th September 2019) - Porporato, Natalia; Baskaran, Mani; Tun, Tin A; Sultana, Rehena; Tan, Marcus; Quah, Joanne HuiMin; Allen, John C; Perera, Shamira; Friedman, David S; Cheng, Ching Yu; Aung, Tin
Abstract : Background/aims: Although being a more objective tool for assessment and follow-up of angle closure, reliability studies have reported a moderate diagnostic performance for anterior segment optical coherence tomography (OCT) technologies when comparing with gonioscopy as the reference standard. We aim to determine factors associated with diagnostic disagreement in angle closure when assessed by anterior segment swept source OCT (SS-OCT, CASIA SS-1000; Tomey, Nagoya, Japan) and gonioscopy. Methods: Cross-sectional study. A total of 2027 phakic subjects aged ≥50 years, with no relevant previous ophthalmic history, were consecutively recruited from a community polyclinic in Singapore. Gonioscopy and SS-OCT (128 radial scans) for the entire circumference of the angle were performed for each subject. A two-quadrant closed gonioscopic definition was used. On SS-OCT images, angle closure was defined as iridotrabecular contact (ITC) to the extent of ≥35%, ≥50% and ≥75% of the circumferential angle. Diagnostic disagreements between both methods, that is, false positives or overcalls and false negatives or undercalls were defined, respectively, as gonioscopic open/closed angles inversely assessed as closed/open by SS-OCT. Results: Two hundred and seventy-two (14.7%) resulted in overcall results (false positives) when ≥50% of the angle circumference was closed using SS-OCT. These eyes had significantly wider (anterior chamber width, 11.7 vs 11.6 mm, p<0.001) and deeper (anterior chamber depth (ACD), 2.4 vs 2.2 mm, p<0.001) anterior chambers than eyes assessed by both methods as closed (true positives). Deeper ACD (OR 9.31) and lower lens vault (LV) (OR 0.04) were significantly associated with a false positive diagnosis in the multivariate analysis. Most of these cases had short (52.6%) or irregular (39%) ITC in SS-OCT images. Conclusions: We found that anterior chamber dimensions, determined by ACD and LV, were factors significantly associated with diagnostic disagreement between anterior segment SS-OCT and gonioscopy in angle closure assessment.